Genomic analysis of the differential response to experimental infection with porcine circovirus 2b. (21st January 2014) - McKnite, A. M.; Bundy, J. W.; Moural, T. W.; Tart, J. K.; Johnson, T. P.; Jobman, E. E.; Barnes, S. Y.; Qiu, J. K.; Peterson, D. A.; Harris, S. P.; Rothschild, M. F.; Galeota, J. A.; et al.
Summary Porcine circovirus type 2 (PCV2) is the etiological agent of a group of associated diseases (PCVAD) that affect production efficiency and can lead to mortality. Using different crossbred lines of pigs, we analyzed host genetic variation of viral load, immune response and weight change following experimental infection with a PCV2b strain (n = 386). Pigs expressed variation in the magnitude and initiation of viremia and immune response recorded weekly until 28 days post‐infection. A higher viral load was correlated with weight gain (r = −0.26, P < 0.0001) and presence of PCV2‐specific antibodies (IgM, r = 0.26–0.34, P < 0.0001; IgG, r = 0.17–0.20, P < 0.01). In genome‐wide association analyses of the responses at different time points, the proportions of phenotypic variation explained by combined effects of 56 433 SNPs were 34.8–59.4% for viremia, 10.1–59.5% for antibody response and 5.6–14.9% for weight change. Relationships between genomic prediction of overall viral load and weight gain during the first weeks of challenge were negative (−0.21 and −0.24 respectively, P < 0.0001). Individuals that carried more favorable alleles across three SNPs on SSC9 (0.60 Mb) and SSC12 (6.8 and 18.2 Mb) partially explained this relationship, having lower viral load (P < 0.0001); lower viremia at day 14 (P < 0.0001), day 21 (P < 0.01) and day 28 (P < 0.05) and greater overall average daily gain during infection (ADGi; P < 0.01), ADGi at week 3 (P < 0.001) and week 4 (P < 0.01). These additive genetic relationships could lead to molecular solutions to improve animal health and reduce production costs.